Effect of education based on the Common-Sense Model of Self-Regulation on blood pressure and self-management of hypertensive patients: A clinical trial study - Zohre Kordvarkane; Khodayar Oshvandi; Younes Mohammadi; Azim Azizi (Elsevier, 2023)
Objective: This study aimed to determine the impact of training based on the Common-Sense Model of Self-Regulation (CSM) on blood pressure and self-management of patients with hypertension. Methods: This randomized controlled trial study was conducted. Seventy-two hypertensive patients were referred to the Farshchian Hospital clinic in Hamadan from April 2021 to March 2022. Samples were selected and randomly assigned to the intervention group (n = 36) and control group (n = 36). The intervention group participated in a training program based on the CSM in five sessions of 30-45 min for one month. Phone follow-up was also done once every three days. The control group only received routine clinic education. The clinic's nurse measured the patients' blood pressure, and the participants completed the self-management questionnaire before and three months after the start of the study. Results: A total of 68 participants completed the study. Results showed that before the intervention, there was no statistically significant difference in the mean scores of self-management and its dimensions, systolic, diastolic, and mean arterial pressure between intervention and control groups (P > 0.05). However, after the intervention, the mean of systolic blood pressure (116.21 ± 14.52 vs. 128.62 ± 16.88) mmHg, mean arterial pressure (88.03 ± 8.47 vs. 98.11 ± 11.69) mmHg and the scores of self-management and its dimensions among patients in the intervention group were decreased comparison with control group (P < 0.05). Conclusions: Education based on the CSM improved self-management and blood pressure reduction in hypertensive patients, so nurses should use it as an effective educational model.